Cross-border population movements and regional economic integration in Latin America. - KRATOCHWIL, K. Hermann (1995)
Notes that present community migration policies provide signals and result in actions which affect labour markets, education systems, social services, science and technology, public security, etc. in both member and non-member countries. Focuses on migration patterns within the Andean Group and within MeERCOSUR.